URGENSI IMPLEMENTASI GREEN ECONOMY DALAM MEWUJUDKAN PEMBANGUNAN BERKELANJUTAN BERBASIS MAQASHID SYARIA’AH - Supriadi Hasibuan (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this research is to briefly examine the meaning of Green Economy and Maqashid Syariah, with the aim that the knowledge index of the people of Sorkam Tengah Village will be better. This study explains these two concepts, the essence of which is how to keep nature in balance. Towards a greener economy is a sustainable goal for every country, including Indonesia. The application of the Green Economy application can reflect the quality of the environment in Indonesia today. Economic, social and environmental like an unbroken cycle of architecture. Environmental quality is highly dependent on economic and social outputs. Maqashid Syariah is a new trend in the study of Ushul Fikh which has developed in the contemporary era. The development of Islamic law in the contemporary era is felt to be more promising when using the methods contained in Maqashid Syariah. As a developmental discipline from ushul fiqh, Maqashid Sharia is now much loved by Islamic law experts for deeper study. Therefore, adequate information is needed about the literature review that discusses Maqashid Syariah from classical to contemporary times. The type of research used to complete the author's journal is of a qualitative type considering that the form of data presentation is descriptive descriptions, with data sources obtained from the general public. direct and indirect (primary and secondary).